2020
DOI: 10.1111/dmcn.14541
|View full text |Cite
|
Sign up to set email alerts
|

Energy consumption does not change after selective dorsal rhizotomy in children with spastic cerebral palsy

Abstract: Aim To determine whether energy consumption changes after selective dorsal rhizotomy (SDR) among children with cerebral palsy (CP). Method We retrospectively evaluated net nondimensional energy consumption during walking among 101 children with bilateral spastic CP who underwent SDR (59 males, 42 females; median age [5th centile, 95th centile] 5y 8mo [4y 2mo, 9y 4mo]) compared to a control group of children with CP who did not undergo SDR. The control group was matched by baseline age, spasticity, and energy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…We found that spasticity does not lead to elevated walking energy. This confirms earlier findings based on matched cohorts and contradicts a widely held view 33 . High energy consumption is a significant problem for individuals with CP; however, spasticity is not the cause.…”
Section: Discussionsupporting
confidence: 83%
“…We found that spasticity does not lead to elevated walking energy. This confirms earlier findings based on matched cohorts and contradicts a widely held view 33 . High energy consumption is a significant problem for individuals with CP; however, spasticity is not the cause.…”
Section: Discussionsupporting
confidence: 83%
“…However, recent research shows that increased oxygen consumption (and associated increased energetics) during walking cannot be solely explained by the degree of inefficiency of gait patterns 10 or the presence of spasticity. 11 Furthermore, independently ambulatory children have stable GMFCS levels as they grow older 12,13 but continue to reduce their capacity for activity and participation in daily activities. 14 Peripheral muscle metabolic factors such as capillarization, mitochondrial content, and function 15,16 are also required for energetics of movement.…”
mentioning
confidence: 99%
“…Six muscle groups were assessed bilaterally: hip flexors, hip adductors, rectus femoris, hamstrings, plantarflexors, and tibialis posterior. We calculated a summary spasticity score by applying polychoric principal component analysis to the bilateral measurements from these six muscles for individuals with complete data (Rozumalski and Schwartz, 2009; Zaino et al, 2020). We used polychoric principal component analysis since standard principal component analysis produces biased estimates with categorical data (Kolenikov and Angeles, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Spasticity is present in up to 91% of children with CP (Odding et al, 2006) and clinicians often believe it causes high metabolic power via inappropriate or prolonged muscle contraction and co-contraction of agonists and antagonists. However, several recent studies have indicated that spasticity reduction does not cause meaningful reductions in metabolic power during walking (Ubhi et al, 2000; Thomas et al, 2004; Bjornson et al, 2007; Munger et al, 2017; Zaino et al, 2020). Reduced metabolic power following spasticity treatment in observational settings likely arises from other factors such as aging.…”
Section: Introductionmentioning
confidence: 99%